Synthesis of 3-((arylsulfonyl)methyl)indolin-2-ones via insertion of sulfur dioxide using anilines as the aryl source. Issue 6 (1st March 2017) - Liu, Tong; Zheng, Danqing; Wu, Jie
Abstract : Facile assembly of 3-((arylsulfonyl)methyl)indolin-2-ones via insertion of sulfur dioxide starting from anilines, N -arylacrylamides and DABCO·(SO2 )2 is realized. Abstract : Facile assembly of 3-((arylsulfonyl)methyl)indolin-2-ones via insertion of sulfur dioxide starting from anilines, N -arylacrylamides and DABCO·(SO2 )2 is developed. This one-pot reaction proceeds efficiently in dichloroethane, leading to sulfonated oxindoles in good yields. Anilines serve as the aryl source, and the in situ generated sulfonyl radicals from sulfur dioxide as the key intermediates are trapped by N -arylacrylamides to provide the corresponding products. Additionally, a broad reaction scope is observed under mild conditions.